A new liquid crystal-based method to study disruption of phospholipid membranes by sodium deoxycholate. Issue 2 (26th January 2017) - An, Zongfu; Wei, Yibin; Jang, Chang-Hyun
ABSTRACT: In this study, we have used liquid crystals (LCs) to investigate the mechanism and dynamics of structural change of phospholipid membranes caused by sodium deoxycholate (NaDC). Addition of the NaDC aqueous solution to the phospholipid [1, 2-dioleoyl-sn-glycero-3-phospho-rac-(1-glycerol) sodium salt (DOPG)] modified aqueous/LC interface resulted in the interaction-induced change of the orientational arrangement of the LCs from a homeotropic state to a planar state. The importance of contributing parameters was determined by observing the changes in the orientation of LCs. We showed that this interaction was affected by reaction time, reaction pH, concentration of NaDC and the presence of cholesterol. Moreover, the phospholipid membrane, which became defective after being exposed to NaDC, was capable of self-repairing by excess Tris-buffered saline solution, indicating that the reaction of NaDC with the phospholipid membrane is reversible. The obtained results proved the feasibility of the method deploying the DOPG/LC interface to monitor the membrane reaction stemming from the interaction between a bioactive molecule and a phospholipid membrane. GRAPHICAL ABSTRACT: